Pre-service teachers' literacy orientation, their reading instruction practices and reading comprehension - Labad, Velma S. (2014)
This study was conducted to find out if relationship exist among (a) literacy orientation, reading instruction practices and reading comprehension of pre-service teachers. Descriptive and correlation research design was utilized. The participants were the 56 pre-service teachers who were randomly selected. Results revealed that pre-service teachers' literacy orientation is similar to an eclectic teacher; their reading instruction practice is a combination of phonics/skills and whole language. Their reading comprehension level is high. Their literacy orientation had no direct influence with their reading instruction practices as well as their reading comprehension. The following recommendations were offered: (a) A seminar-workshop should be conducted to all reading teachers specifically those handling reading subjects in the College of Education. (b) A curriculum (the subject on teaching reading) revisit should be done to find out how to develop the literacy orientation and reading instruction practices of the pre-service teachers that would have an impact in the learning and teaching of reading among the elementary students; and (c) A follow up of this research should be done to get a clearer picture of the literacy beliefs and practices of the pre-service teachers. A qualitative research is in order. This will give pre-service teachers a chance to express their beliefs and practices either in the form of an interview or a classroom visit rather than simply answering a questionnaire.
Keywords: Literacy orientation; Reading comprehension; Literacy instruction practices